MAPPING SITE AMPLIFICATION BY SURFACE SEDIMENTS OF BOGOR REGION USING MICROTREMOR METHOD - Faiz Aldiza, Muhammad
The city of Bogor is an area that is vulnerable to earthquake threats due to the active fault activity which is quite a lot, including the Cimandiri fault and the Citarik fault. One of the factors that trigger damage due to earthquakes is site amplification in an area. This site amplification, affects how much amplification is generated when a wave passes through the region. Measurement of microtremor data was carried out in Bogor City to determine the amplification site based on natural frequency (f0), dominant period (T0). Analysis of microtremor data using the HVSR method with geopsy software to obtain the main parameter, namely f0 which is used to obtain the dominant period of the soil. Then modeling was carried out to obtain the value of Vs on the surface sediment and bedrock, and the value of the thickness of the soft sediment (h) from the frequency parameter and also the speed of the S wave was obtained. After getting the value of h, the site amplification value was obtained using the HV-Explorer software which has been weighted based on SNI 1729 in 2019. The results of the study show that the dominant period of the soil is spread between 0.08 – 0.92 s; the value of Vs surface sediment ranges from 116.82 – 288 m/s; the value of Vs bedrock sediment ranges from 252 – 700 m/s; the value of the thickness of the soft sediment ranges from 4.1 to 28.1 m; and site amplification ranges from 1.1 – 1.5 times. 6. Based on the characteristics of the dynamics of the soil, the research area which includes Tanah Sareal District, East Ciomas Region, North Bogor, West Sukaraja, Central Bogor, and Southern and North East Bogor has the potential for greater damage than other areas of the city of Bogor. The recommended area for development is the South Bogor area, and besides that, special attention is needed in carrying out development.